Implementasi Aplikasi Setara Daring Dalam Pembelajaran Pendidikan Agama Islam Pada Program Paket C di PKBM Bangkit Semarang - Bakti Fatwa Anbiya; irfaan (Center of Education Journal (CEJou), 2023)
The online seTARA application is a Learning Management System application, a technological development in the form of software that functions to conduct, plan, and also provide assessments in specific learning processes. This research is of a qualitative descriptive type with the type of data used in the form of primary data and secondary data. Primary data is data obtained from the field by researchers, secondary data is data obtained from primary data. This article aims to describe the Implementation of Online Equivalent Applications in Learning Islamic Religious Education in the Package C Program at PKBM Bangkit Semarang. The results showed that PKBM Bangkit chose applications provided by the directorate of community education and special education, namely online equivalent applications. The advantage in using the application is that the online SeTARA application makes it easier for tutors and residents to learn in the learning process, while the disadvantages are visible: The low relationship between tutors and residents learning so that it will affect the formation of character in the teaching and learning process